(untitled) (Applied Biological Research, 2018)
The present study was aimed to develop bottle gourd-strawberry blended toffee and assess the changes in its chemical composition and sensory properties during storage. The bottle gourd and strawberry pulps weremixed and heated till reduced by half. Ingredients like sugar, glucose, butter and skim milk powder were added and the contents cooked until TSS of 78° Brix was achieved. The cooked mass was moulded into toffee and wrapped in butter paper and transparent plastic film and packed in laminated pouches before stored in air-tight jars under ambient conditions (37±5°C) for 90 days. Maximum phosphorus content of 23.4 mg 100 g-1 was noticed in 0:100::bottle gourd: strawberry treatment while maximum calcium content of 26.33 mg 100 g-1 was observed in 100:0::bottle gourd: strawberry treatment. The antioxidant content in bottle gourd-strawberry blended toffee decreased with the advancement in storage period. Maximum total phenol and anthocyanin contents were found in 0:100::bottle gourd: strawberry. No microbial contamination was found upto 60 days, but after 90 days of storage the highest microbial count of 0.46 × 104 cfu was found in 100:0: bottle gourd: strawberry. The 30:70::bottle gourd: strawberry treatment gave highest score for colour (8.34), flavour (8.29) and taste (8.23). Overall, 30:70:: bottle gourd: strawberry treatment proved superior over other combinations with respect to sensory attributes. However, the prepared toffees were acceptable after 90 days of storage under ambient conditions.